Handbook of laboratory animal management and welfare - Wolfensohn, Sarah; Lloyd, Maggie (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
"This bestseller has been an essential book for all those working with laboratory animals since it was first published in 1994. This fourth edition retains all the classic features that have made it a must-have reference including emphasis on best practice in order to improve animal welfare. The contents have been thoroughly updated and reorganised to make sure it is a really practical book for day-to-day use in the laboratory. The first section of the book covers principles applicable to all species, for example husbandry, handling and the education and training required by scientists and technical staff working with animals in the laboratory. Later chapters focus on specific species or groups of species. New to this edition: Reflects changes in European legislation and their impact on national legislation. Covers recommendations for the education and training of those carrying out animal experiments across Europe. New chapters on ethical considerations and balancing animal welfare with science. New information on environmental enrichment for laboratory animals. Covers advancements in anaesthesia and analgesia and techniques. Spiral bound for ease-of-use as a bench-top reference. This book is ideal for all personnel carrying out scientific procedures using animals, particularly during training and also for the new researcher. It will also be essential reading for study directors designing research programmes, animal technicians and veterinarians working with laboratory animal species"--Provided by publisher.
Education and training for the personal licence holder -- Ethical considerations around using animals in research -- The regulatory framework -- Balancing animal welfare with science -- Animal husbandry, environmental enrichment, and occupational health and safety -- Principles of animal use and experimental design -- Handling and techniques -- Humane methods of killing -- Anaesthesia and analgesia -- Introduction to surgery and surgical techniques -- Small laboratory animals -- Carnivores -- Primates -- Production (farm) animals / C.J. Trower -- Wild animals -- Aquatic species.
Includes bibliographical references and index.
Keywords: Animal Welfare; Animals, Laboratory